Intersectional stigma and psychosocial well-being among MSM living with HIV in Guangxi, China. Issue 2 (13th May 2020) - Yang, Xueying; Li, Xiaoming; Qiao, Shan; Li, Linda; Parker, Casey; Shen, Zhiyong; Zhou, Yuejiao
ABSTRACT: The existing literature suggests a negative impact of intersectional stigma on multiple aspects of psychosocial well-being among individuals with multiple stigmatized identities. However, such impact remains poorly understood. This study aims to investigate the association between intersectional stigma and psychosocial well-being among 193 men who have sex with men (MSM) living with HIV. Based on their responses to measures of HIV-related stigma and sexual and gender minority (SGM) stigma, the participants were grouped into "high" vs "low" on each type of stigma. The General Linear Model (GLM) was used to analyze the main and interaction effect of two types of stigma on multiple psychosocial measures. Our results indicated a significant interaction effect of two types of stigma on depression, anxiety, quality of life, and psychological resilience after controlling for key socio-demographic covariates. The findings suggest that experiencing both HIV-related stigma and SGM stigma may synergistically lead to poor psychosocial well-being among MSM in a more profound manner than experiencing only one type of stigma. It is critical for researchers and clinicians to consider the patients' multiple stigmatized identities, develop effective intervention strategies, and improve the psychosocial well-being of MSM living with HIV in China and other cultural settings.